Additional probation period foreseen to order the execution of penalty (Ius Novum, 2019)
The article analyses a legal nature of additional six-month since the end of the operational period foreseen to issue a decision on activating a suspended sentence (Article 75 § 4 CC), the method of calculating this time limit and the moment when the decision on executing the penalty is enforceable. The author considers that this time limit is of substantial nature, as it is regulated in the Criminal Code and it is related with substantial requirements for executing the penalty. To calculate the time limit, the computatio civilis method should be applied, which consists in counting its running on a day-to-day basis (dies a qua) as the beginning of operational period is determined by a final sentence, i.e. the institution regulated in criminal procedure law. The time limit for activating the suspended sentence is valid if in the case of the discretionary sentence activation (Article 75 § 2 and 3 CC) a decision is issued and it is final before the expiry of six months following the end of the operational period (Article 178 § 5 EPC), and in the case of mandatory activation of the sentence, it is sufficient that such decision is issued within the said time limit (Article 9 § 3 EPC).
Keywords: penalty of deprivation of liberty; operational period; time limit; conditional suspension; decision on activating a suspended sentence